2019
DOI: 10.1186/s12889-019-6874-2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of cervical cancer prevention among Zambian women and men

Abstract: Background In Zambia, cervical cancer screening was started in 2006 and the human papillomavirus vaccine was piloted in 2013. Nevertheless, cervical cancer remains the leading cancer. It is assumed that knowledge, social interaction, health behaviors and religion are factors that can influence screening and vaccination practices. This study addresses the question, what is the relationship between knowledge about cervical cancer, attitudes, self-reported behavior, and immediate support system, towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
4
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 24 publications
7
33
4
5
Order By: Relevance
“…Among the 1,376 participants involved in this survey, 1,240 participants (90.1%) representing 456 males (33.1%) and 784 females (57.0%) were aware of the terminology "cervical cancer." When stratified by gender, women had significantly greater knowledge, compared to men in terms of "cervical cancer being common in middle age (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) females" (75.5 vs. 67.5%, respectively, p ≤ 0.001). These participants were examined further to test their knowledge on some risk factors and symptoms of cervical cancer, as presented in Tables 2-4.…”
Section: Knowledge About Cervical Cancermentioning
confidence: 99%
“…Among the 1,376 participants involved in this survey, 1,240 participants (90.1%) representing 456 males (33.1%) and 784 females (57.0%) were aware of the terminology "cervical cancer." When stratified by gender, women had significantly greater knowledge, compared to men in terms of "cervical cancer being common in middle age (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) females" (75.5 vs. 67.5%, respectively, p ≤ 0.001). These participants were examined further to test their knowledge on some risk factors and symptoms of cervical cancer, as presented in Tables 2-4.…”
Section: Knowledge About Cervical Cancermentioning
confidence: 99%
“…Available data from the rst three years of the vaccination program showed that it failed to meet its target of vaccinating 50,000 girls every year (11). More recently, a study on Zambian parents in Lusaka found that 41% of their participants did not support the vaccination (12), and only 6.7% of participants in another study had vaccinated their daughters (13).…”
Section: Hpv Vaccination In Zambiamentioning
confidence: 99%
“…The disconnect between supply and demand has been attributed to a lack of knowledge surrounding the vaccine's indication, e cacy and safety (13), as well as a lack of community engagement to address concerns and misunderstandings, particularly in rural districts (11,14). Women's limited decision-making power compared to their husbands regarding their daughters receiving the HPV vaccination, coupled with a lack of engagement with male community members during the vaccine's roll-out has also been attributed to low uptake (15,16).…”
Section: Hpv Vaccination In Zambiamentioning
confidence: 99%
See 2 more Smart Citations